Impact of Vegetable Integrated Pest Management Farmer Field School Programme in Sub-Tropical Region of Jammu and Kashmir - Rakesh Sharma and Rajinder Peshin, (Indian Journal of Extension Education, 2015)
Afield study was conducted to evaluate the impact of vegetable Integrated Pest Management- farmer Field School (IPMFFS) Programme in the sub-tropical Jammu region of the state of Jammu and Kashmir (J&K). Ex-post facto with-withoutresearch design was employed to for conducting the impact evaluation. A sample of 80 IPM-trained and 60 non-IPMfarmers were selected for the study. IPM practices namely raised nursery beds in cabbage (p=0.026), timelytransplantation of cauliflower (p=0.034), collection of eggs and egg masses of insect pests (p=0.048) were adopted bysignificant proportion of IPM trained farmers. A logistic regression model was fitted which showed IPM trainingprogramme impacted adoption of IPM practices namely deep ploughing and collection of insect pest eggs and eggmasses. IPM training did not influence adoption of other cultural and mechanical practices. IPM trained farmers decisionof pesticide use was not influenced by IPM training.